2021
DOI: 10.25115/eea.v39i5.5074
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence as the Basis for the Development of Organizational Leadership During the Covid Period (Educational Institution Case)

Abstract: The period of coronavirus disease pandemic caused new challenges in leadership development and reflected transition to collective leadership as the most effective method. Because (emotional) unity of the corporate team (which is practically realized in collective leadership) is a primary factor for overcoming the crisis, human resources will be saved as much as possible in this context. The use of emotional intelligence tools and organizational leadership development becomes highly relevant. The emphasis is pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…However, some studies show that the loss of control is a positive sign, arguing that exercising excessive control is tantamount to micro-management and is often counterproductive ( Lee, 2021 ). Our analysis further indicates that employing emotional intelligence ( Semenets-Orlova et al, 2021 ), adopting authentic and empathetic leadership styles, and changing supervisory mindset are crucial for the effective and successful implementation of remote work strategies ( Antonacopoulou and Georgiadou, 2021 , Bartsch et al, 2021 ). We found that some studies advocate that organizations should further develop leadership behaviors through more effective training ( Hughes, 2021 ) and organizational inclusion techniques, by way of which everyone feels a sense of belonging, respect, and appreciation for who they are as individuals ( Bennett et al, 2021 , Kuknor and Bhattacharya, 2021 ).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, some studies show that the loss of control is a positive sign, arguing that exercising excessive control is tantamount to micro-management and is often counterproductive ( Lee, 2021 ). Our analysis further indicates that employing emotional intelligence ( Semenets-Orlova et al, 2021 ), adopting authentic and empathetic leadership styles, and changing supervisory mindset are crucial for the effective and successful implementation of remote work strategies ( Antonacopoulou and Georgiadou, 2021 , Bartsch et al, 2021 ). We found that some studies advocate that organizations should further develop leadership behaviors through more effective training ( Hughes, 2021 ) and organizational inclusion techniques, by way of which everyone feels a sense of belonging, respect, and appreciation for who they are as individuals ( Bennett et al, 2021 , Kuknor and Bhattacharya, 2021 ).…”
Section: Resultsmentioning
confidence: 81%
“…The second topic in this category—remote work management (Topic 7)—offers a more focused understanding of managerial and leadership roles in relation to remote work strategies. Such studies investigate issues such as job satisfaction ( Karani et al, 2021 ), the perceived influence of the managers in the form of control, exploitation, and work engagement ( Khan, 2021 ), and the need to develop new leadership capabilities ( Antonacopoulou and Georgiadou, 2021 , Kirchner et al, 2021 , Semenets-Orlova et al, 2021 ). Decision making concerning overcoming remote work-related challenges and their solutions also received some attention ( Hughes, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erpenbeck and Rosenstiel (2003) consider social competence as one of the four types of competences and define it as a person's inclination to communicate and cooperate (understanding others, developing others, service orientation, using diversity, political awareness, influence, communication, negotiation and disagreement resolution, leadership, catalyst for change, networking, cooperation and collaboration, teamwork). Emotional intelligence as a component of social competence was considered as a basis for the development of organizational leadership during the Covid period in educational institutions (Semenets-Orlova et al, 2021) and can be applied to the target group of young scientists. Particular attention was paid to educational changes (Semenets-Orlova, 2017) as a driver of social competence transformation.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Recently, more and more scholars [8,9] have begun to pay attention to the culture in the organization, more and more publications on this problem [10] appear in the scientific lit erature, but it is still not clear what "organizational culture" and "business culture" are, what the difference between these two terms is, and which varieties it has. Therefore, first of all it is necessary to form evaluation characteristics, indicators, norms and methods of evaluation of organizational culture.…”
mentioning
confidence: 99%